Multilingual broadcasting in post-2000 Zimbabwe: design, implementation and language parity - Mpofu, Phillip; Mutasa, Davie E.; Salawu, Abiodun (Routledge, 2022)
Zimbabwe’s Broadcasting Services Amendment Act (BSAA; 2007) unveils a commitment towards multilingual broadcasting for public broadcasting. This study cross-examines the design of the multilingual broadcasting policy in the Act, and its subsequent implementation at the Zimbabwe Broadcasting Corporation (ZBC), with particular attention to the treatment of indigenous languages. Empirical data for this study is drawn from purposively selected broadcasting personnel, academics and radio/television audiences. The study is grounded in the concepts of linguistic hegemony, political economy of communication and media economics. The study shows that the implementation of the multilingual broadcasting policy apparent in the BSAA (2007) is restricted by the sociolinguistic, political, economic and global factors which determine language choices and practices in broadcast media. This study is a significant contribution to the meagre scholarship on the nexus between language and media policy, particularly language policy of broadcast media in Zimbabwe, and Africa in general.